Image analysis on migration of non aqueous phase liquid in combined single and double porosity media - Sim, Mei Chee (2017)
Transportation, storage as well as management of environmentally hazardous fluid compounds are essential for chemical and petroleum industries. Many of these compounds form a different fluid phase when in contact with water due to their extremely low solubility in water. They are known as non-aqueous phase liquids (NAPLs). NAPLs can get into contact with the environment due to accidental spills during transportation processes or as a result of leakage in pipes or underground tanks. Generally, there are two types of NAPLs that can bring contamination to the subsurface environments and they are light non-aqueous phase liquids (LNAPLs) and dense non-aqueous phase liquids (DNAPLs). Therefore, it is important to study the migration of NAPLs in the soil. The main purpose of this research is to study the flow pattern of NAPLs and investigate the difference in LNAPL and DNAPL flow characteristics in combined single and double porosity layered soil. Toluene was used as the LNAPL whereas trichloroethylene represented the DNAPL. Single porosity soil was represented by 0.15mm sized sand whereas aggregated kaolin was used as the double porosity media. Two layers of sand and two layers of aggregated kaolin were placed alternately with sand as the bottom layer. NAPL was then poured into the acrylic model with the media prepared earlier and then DSLR camera was used to capture the images and finally Image-Pro software used for image analysis. The migration of both NAPLs was analyzed through the images captured based on data processing using the Image-Pro software. In conclusion, the migration of NAPLs is much faster in double porosity aggregated kaolin compared to the migration of NAPLs in single porosity sand. It is also concluded that toluene, which is the LNAPL used in this research, will take a longer time to be fully spread throughout the media as compared to the DNAPL trichloroethylene used in this research. The higher density of DNAPL will cause the gravitational force to become bigger to pull the NAPL droplets downwards. Trichloroethylene is able to migrate deeper as it is denser than water as compared to toluene.